The Political Ecology of Hedgerows and Their Relationship to Agroecology and Food Sovereignty in the UK - Mark Tilzey (Frontiers in Sustainable Food Systems, 2021)
Hedgerows can make an important contribution to agroecological transitions and to an overall contribution to multifunctional agro-ecosystems with multiple benefits for biodiversity, climate change mitigation, soil health, human health, well-being, and livelihoods. Where such agroecological transition assumes the form of political agroecology, this can underpin transformation of the farming system towards food sovereignty. Current mismanagement of hedgerows is constraining the optimum delivery of ecosystem services by these important features of the British landscape. This mismanagement is, moreover, an integral part of a (capitalist) productivist degradation of the countryside that is contributing to the delivery of ecosystem disservices and is, therefore, antithetical to the adoption of agroecological production practises. Being contrary to the requirements of political agroecology, it is similarly antithetical to the requirements of food sovereignty. In response, this paper outlines what appears to be required, in policy and political terms, for the adoption of an agroecological and food sovereignty framework enabling the sustainable management of hedgerows and maximising their potential for ecosystem services delivery.